A Tunable Hexa-Band SRR Metamaterial for Microwave Sensing Application - Md. Zikrul Bari Chowdhury; Mohammad Tariqul Islam; Ismail Hossain; Ahmed Alzamil; Md. Samsuzzaman (Ain Shams Engineering Journal)
The study explores a novel hexa-band metamaterial utilizing tunable split ring resonators for wireless communication and sensing applications. The proposed metamaterial structure demonstrates remarkable versatility through its hexa-band resonant behavior and adaptability, achieved by incorporating tunable split ring resonators. The proposed MTM unit cell is characterized by electrical measurements of 0.122λ0 × 0.122 λ0, where λ0 corresponds to the wavelength calculated at a resonance frequency of 2.53 GHz, leading to a total dimension of 14.5 × 14.5 mm2. It has six transmission coefficients (S21), they cover the S, C, X, and Ku bands at the resonating points of 2.53 GHz, 4.12 GHz, 7.17 GHz, 10.31 GHz, 12.18 GHz, and 14.26 GHz, respectively. The design offers flexibility for frequency-selective applications in wireless communication due to its small size, high refractive index, and the feature that it can provide frequency selectivity by tuning. Different solid materials, earth materials, hydrocarbon, and Arlon substrates are used for sensing applications. The proposed metamaterial offers greater flexibility and adaptability due to the incorporation of tunable split ring resonators. This makes it suitable for various wireless communication and sensing applications.